Recent trends in power engineering : selected, peer reviewed papers from the 2015 9th International Power Engineering and Optimization Conference (PEOCO 2015), March 18-19, 2015, Melaka, Malaysia - Musirin, Ismail; Sulaiman, Shahril Irwan (Applied mechanics and materials, 2015)
Collection of selected, peer reviewed papers from the 2015 9th International Power Engineering and Optimization Conference (PEOCO2015), March 18-19, 2015, Melaka, Malaysia. The 141 papers are grouped as follows: Chapter 1: Applications of Artificial Intelligence in Power Engineering; Chapter 2: Electrical Drives and Power Electronics; Chapter 3: Electrical Machines and Apparatus;Chapter 4: Quality and Reliability of Power, Protection and Electromagnetic Compatibility in Power Systems; Chapter 5: Planning, Operation and Economics of Power Systems; Chapter 6: Energy Policy and Engineering Management of Renewable Energy Systems;Chapter 7: Applied Decisions in Energy and Power Research Keyword: Computer and AI Applications in Power Engineering; Current Engineering Issues and Industrial Experience; Electrical Drives & Amp; Power Electronics; Electrical Machines Design; Energy, Power Sources and Storage; Power Quality, Protection and Electromagnetic Compatibility; Power System Dynamic, Stability and Control; Power System Planning, Operation and Economics; Renewable Energy, Energy Efficiency and Energy Policy; Power System Transmission & Distribution.